Analysis of the Role of Socialization, Experience and Perception of Nurses on the Application of Occupational Safety and Health - Wijaya, Muhammad Irzal; Indasah, Indasah; Dewi K, Prima (Babali Nursing Research, 2023)
Introduction: Occupational Health and Safety (K3) is an effort in order to ensure the integrity and perfection of both physical and spiritual labor, their work and culture towards a prosperous and prosperous society. The purpose of implementing K3 is for workers to obtain a high degree of health, both in terms of physical, mental, and social with various efforts made. The purpose of the study was to analyze the influence of the role of socialization, experience and perception of nurses on the implementation of the occupational health and safety management system at Taman Husada Bontang Hospital. Methods: Quantitative research design with observational analytic research methods cross-sectional approach. The population of all nurses at Taman Husada Bontang Hospital was 252 respondents. The sample of some nurses at Taman Husada Bontang Hospital was 154 respondents with proportional random sampling. Independent variables of socialization roles, experiences, and perceptions of nurses. The dependent variable of the implementation of the occupational health and safety management system. Results: The results of the study using linear regression analysis (R Square = 0.058) showed the influence of socialization role variables (p = 0.029), and there was no influence of experience variables (p = 0.339) and nurse perceptions (p = 0.172) on the application of occupational safety and health. The results of the multivariate analysis showed that the most influential variable on the application of occupational safety and health was the role of socialization (p = 0.029 and B = 0.240). Conclusion: It is expected that nurses should continue to develop knowledge and skills in the field of nursing management, especially related to Occupational Health and Safety (K3) so that the services provided can be more optimal and of high quality without forgetting the level of health and safety for nursing care providers.